Evaluation of the Fluconazole Prophylaxis against Fungal Colonization in the Preterm Neonates: A Double-blind Clinical Trial - Sara Amini; Gholamreza Pouladfar; Fatemeh Ghasemi; Hadis Jafarian; Parisa Badiee (Mashhad University of Medical Sciences, 2024)
Background: Our study aimed to compare the twice-weekly and three-time weekly prophylactic fluconazole regimens among low birth weight premature neonates. Methods: Premature neonates (40 cases) were divided into two groups and received two and three-times-weekly fluconazole regimens for three weeks. Surveillance of fungal colonization was performed before treatment and twice weekly. Results: Fungal colonization occurred in 11 infants in group A and 4 infants in group B (55% vs. 20%, p=0.022). In both groups, the rectum was the most common site of colonization. Candida glabrata, Candida orthopsilosis and, Candida albicans were the most commonly isolated species in both groups. There were no significant differences between the two groups regarding birth weight, gestational age, and other baseline risk factors for fungal colonization. Conclusion: In this study, the three-times-weekly administration of prophylactic fluconazole appears to be more effective in preventing fungal colonization than the twice-weekly regimen among premature neonates.